The Effect of Aerobic Exercise and Pomegranate Juice Consumption on Serum Enzyme Levels Associated With the Oxidant-Antioxidant System of Women Rescued From Breast Cancer - Babak Rouzbehan; Hossein Abed Natanzi; Khosro Ebrahim; Farshad Ghazalian (Mashhad University of Medical Sciences, 2021)
Introduction: Increasing oxidative factors and reducing antioxidants is one of the main causes of breast cancer.The purpose of this study was to investigate the effect of eight weeks of aerobic exercise and pomegranate juice on serum enzyme levels related to the Oxidant-Antioxidant system of women saved from breast cancer. Methods: In this blinded randomized control trial which was conducted in rasht in 2019, 40 women with breast cancer were selected who were randomly were assigned into four equal groups control groups (n=10), pomegranate juice (n=10), aerobic exercise (n=10) and aerobic exercise and pomegranate juice (n=10). The aerobic exercise group and the aerobic exercise and pomegranate juice group, performed training programs including 8 weeks and 3 sessions per week with intensity 50 to 70% of the maximal heart rate for 60 to 90 minutes of training. Two groups of pomegranate juice consumers received 100 cc of pomegranate juice before each training session. In order to investigate the variables of research (MDA, SOD, GPX), blood samples were collected 48 hours before and after the intervention in fasting state. The obtained data was analyzed using of one-way analysis of variance (ANOVA) and bonferroni post hoc test analysis. The significant level was P<0/05 Results: The results showed that 8 weeks of aerobic exercise caused a significantly decreased MDA levels and significantly increased SOD and GPX levels in women with breast cancer (P = 0/0001).aerobic exercise without use of pomegranate juice, only led to a significant decrease in MDA (P=0.0001) level, and pomegranate juice consumption alone, no significant changes were observed at the three variables investigated in women with breast cancer. Conclusion: According to the results, Aerobic exercise and consumption of pomegranate juice simultaneously, reduce oxidative factors and increase anti-oxidant factors in women Rescued from Breast Cancer